Anaplastic oligodendroglioma: a new treatment paradigm and current controversies - Roth, Patrick; Wick, Wolfgang; Weller, Michael (Current treatment options in oncology, 2013)
Anaplastic oligodendroglial tumors have gained increasing interest with the emerging role of molecular markers and systemic chemotherapy during the past years. The long-term results of two landmark trials, RTOG 9402 and EORTC 26961, have resulted in a reconsideration of the appropriate therapeutic approaches for patients with these tumors. Both trials indicate that patients whose tumors harbor a 1p/19q co-deletion benefit particularly from the addition of procarbazine/lomustine (CCNU)/vincristine (PCV) chemotherapy to radiation therapy (RT). The median survival of patients with co-deleted tumors treated within the RTOG trial with PCV before irradiation was 14.7 years compared with 7.3 years of patients who received RT alone. Median overall survival has not been reached in the RT plus PCV arm of the EORTC trial, but a similar difference can be anticipated after a follow-up of more than 12 years. In contrast, no such benefit was observed for patients with tumors lacking 1p/19q co-deletion. Outside clinical trials, patients with anaplastic oligodendroglial tumors, and 1p/19q co-deletion therefore should be offered a combined treatment modality regimen, including radio- and chemotherapy. PCV, however, is associated with significant hematological toxicity and also nonhematological side effects, which probably translate into reduced quality of life for long-term survivors. Therefore, it might be warranted to replace PCV by temozolomide, which displays a more favorable side effect profile. Data from the NOA-04 study suggest that PCV and temozolomide have similar effects. However, long-term data on the benefit from temozolomide are lacking, making a definite answer on the equivalence of temozolomide and PCV in anaplastic oligodendroglioma (AO) impossible. The current evidence precludes RT alone for AO patients. Neither the RTOG nor the EORTC trial defined the role of chemotherapy alone. A comparison of combined modality treatment with chemotherapy alone followed by RT at progression is pending. Long-term follow-up of NOA-04 patients and results from future trials may help to clarify these questions. With more and more AO patients living 10 years or more, particular attention must be paid to late side effects, such as neurotoxicity, and careful monitoring is required for all treated patients.